REPRESENTASI MAKNA TANDA/SIMBOL DALAM FILM VICTOR FRANKENSTEIN (2004) KARYA MARY SHELLEY - Nensilianti, Nensilianti; Yuliana, Yuliana; Ridwan, Ridwan (University of Brawijaya, 2024)
Frankenstein is a 2004 American horror film adapted from the 1818 novel Frankenstein by Mary Wollstonecraft Shelley; or, Modern Prometheus. This film tells the story of a scientist, namely Victor Frankenstein, whose ambition is to create life. Victor Frankenstein's ambition unknowingly brought havoc in his life. Victor Frankenstein is a Swiss natural sciences student who resurrects artificial humans made from dead body parts using an electroshock device. Everyone his creation meets including himself is motivated to hate him. The monster, abandoned and lonely, attacks its maker, who eventually perishes. In this study, the authors examine the representation of the meaning of symbols in the 2004 Victor Frankenstein film using Charles Sanders Pierce's semiotic approach. Researchers used descriptive qualitative research methods. The descriptive qualitative research method is research that tends to use analysis and focuses on in-depth observations. The results of this study indicate that the researcher found 17 symbols with different meanings in the